Public art and fictional works: simultaneously commemorating fiction and reality - Holloway, Johan (2024)
Since 1837, there has been an increasing number of public art installations in Britain that simultaneously commemorate fiction and reality, be they officially or unofficially produced. The official examples intentionally commemorate fictional works, so as to simultaneously commemorate real people or places that are relevant to those works. Official examples have commemorated fictional stories and characters to celebrate: the authors of those works; the places where those authors are from, or where they created their represented works; the places where those works were produced; or the cultural output of Britain as a whole. The unofficial examples, however, intentionally appropriate public spaces to specifically commemorate fictional characters that are relevant to those spaces. Such unofficial examples subsequently endure if the official owner of the appropriated site allows the inadvertent commemoration of their site to persist.